Correction: Jin et al. A pH-Responsive DNA Tetrahedron/Methotrexate Drug Delivery System Used for Rheumatoid Arthritis Treatment. J. Funct. Biomater. 2023, 14, 541 - Yi Jin; Xingyu Ge; Yinjin Xu; Siyi Wang; Qian Lu; Aidong Deng; Jingjing Li; Zhifeng Gu (Journal of Functional Biomaterials)
In the original publication [...]